Uji Mutu Fisik Sediaan Sabun Padat Transparan Dari Kulit Buah Pisang Ambon (Musa paradisiaca var. Sapienthum L.) - Ananda Ramadani; Dwi Putri Indah S (Lumbung Farmasi: Jurnal Ilmu Kefarmasian, 2023)
Soap serves to move dirt from the surface of the skin, floor, or fabric, does not damage the skin and is able to protect the skin from the effects of free radicals. Compounds that are able to ward off free radicals are antioxidants and are sourced from the Ambon banana plant (Musa Paradisiacar .VarSapienthum L). This study aims to make transparent solid soap from Ambon banana peel extract (Musa Paradisiacar. VarSapienthum L) with good physical quality. The formula used in the form of extract concentrations of 5% and 10% by using a type of laboratory experimental research by making transparent solid soap from the peel extract of the Ambon banana fruit (Musa Paradisiacar.VarSapienthum L) and by using the maceration method. Tests were carried out on organoleptic aspects as well as physical quality tests including pH, foam stability, and transparency. The results of the observation of the pH test with a concentration of 5% 12, and a concentration of 10%, namely 10. The results of the research on making transparent solid soap from the extract of the Ambon banana peel met the requirements for foam stability, transparency, and irritation but did not meet the requirements for the pH test.